Teaching Indigenous Language Revitalization over Zoom - Daurio, Maya; Turin, Mark (KULA)

(untitled) (University of Victoria Libraries, 2022)
In this teaching reflection, co-authored by an instructor and a teaching assistant, we consider some of the unanticipated openings for deeper engagement that the “pivot” to online teaching provided as we planned and then delivered an introductory course on Indigenous language documentation, conservation, and revitalization from September to December 2020. We engage with the fast-growing literature on the shift to online teaching and contribute to an emerging scholarship on language revitalization mediated by digital technologies that predates the global pandemic and will endure beyond it. Our commentary covers our preparation over the summer months of 2020 and our adaptation to an entirely online learning management system, including integrating what we had learned from educational resources, academic research, and colleagues. We highlight how we cultivated a learning environment centered around flexibility, compassion, and responsiveness, while acknowledging the challenges of this new arrangement for instructors and students alike. Finally, as we reflect on some of the productive aspects of the online teaching environment—including adaptable technologies, flipped classrooms, and the balance between synchronous and asynchronous class meetings—we ask which of these may be constructively incorporated into face-to-face classrooms when in-person teaching resumes once more.